Establishment: Some Theological Considerations. (September 2019) - Brown, Malcolm
Abstract : Liberal modernity and its associated individualism have created conditions in which a case for an established Church appears to contradict all the principles of social diversity. But the characteristic mechanisms of liberal modernity for managing difference – the ballot and the market – have proved inadequate to prevent social divisions from deepening, as the national argument about Brexit demonstrates. Despite the Church of England's lack of a confident narrative of establishment and the tendency to evaluate establishment on pragmatic grounds, this article proposes that a robust theological defence of establishment can be made in terms of both Anglican ecclesiology and a theology of power and authority in which the highest sources of authority are those with the least power. Whether the Church of England is able to regain confidence in such a theology of establishment and rise to the challenge of generating a unifying national narrative of identity post-Brexit, is left as an open question.